Thirteen; Stones Around the Fire; the Threshold: Myth and Discourse on the Genesis of Architecture - James Samuel Jones (Oz, 1991)
The number 13 reminds us of the "other," that which is mysterious, beyond reason, unknown, and only suggested through myth. The number 13 is mystical because it marks such a significant point in the counting of things; therefore it is with 13 that the realm of the unknown starts - the realm where things must be counted to be valued.